Unusual electrode-dependent deformation of 3Y-TZP induced by weak electric current in oxygen-lean atmosphere. (December 2021) - Wang, Kang; Chen, Guoqing; Wang, Qi; Fu, Xuesong; Zhou, Wenlong
Abstract: The plastic deformation behavior of 3Y-TZP with weak electric current in oxygen-lean atmosphere was investigated. The results demonstrated that a weak electric current ( I =1 A) can significantly promote the plastic deformation of 3Y-TZP at furnace temperature of 1200 °C and a strain rate of 6.67 × 10 −4  s −1 . As the electric current increases (1–5 A), the flow stress of plastic deformation has a significant decrease. Especially, a remarkable electrode-dependent deformation near the cathode side was observed for the first time. This unusual phenomenon is mainly attributed to the enhancement of the cation diffusion caused by the electric current-induced electrochemical reduction reaction. In addition, this phenomenon may provide a new method to control the local plastic deformation by controlling the electrode direction and the deformation atmosphere. Graphical abstract: Image, graphical abstract